HM71224, a novel Bruton's tyrosine kinase inhibitor, suppresses B cell and monocyte activation and ameliorates arthritis in a mouse model: a potential drug for rheumatoid arthritis. Issue 1 (December 2016) - Park, Jin; Byun, Joo-Yun; Park, Ji; Kim, Yu-Yon; Lee, Ye; Oh, Jeong; Jang, Sun; Kim, Young; Song, Yeong; Son, Jeewoong; Suh, Kwee; Lee, Young-Mi; et al.
Abstract Background Bruton's tyrosine kinase (Btk) is critical for activation of B cells and myeloid cells. This study aimed to characterize the effects of HM71224, a novel Btk inhibitor, bothin vitro and in a mouse model of experimental arthritis. Methods The kinase inhibition profile of HM71224 was analyzed. The in vitro effects of HM71224 on B cells and monocytes were analyzed by examining phosphorylation of Btk and its downstream signaling molecules, along with cytokine production and osteoclast formation. The in vivo effects of HM71224 were investigated in a mouse model of collagen-induced arthritis (CIA). Results HM71224 irreversibly bound to and inhibited Btk (IC50  = 1.95 nM). The compound also inhibited the phosphorylation of Btk and its downstream molecules such as PLCγ2, in activated Ramos B lymphoma cells and primary human B cells in a dose-dependent manner. Furthermore, HM71224 effectively inhibited the production of tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β by human monocytes, and osteoclast formation by human monocytes. Finally, HM71224 improved experimental arthritis and prevented joint destruction in a murine model of CIA. Conclusions HM71224 inhibits Btk in B cells and monocytes and ameliorates experimental arthritis in a mouse model. Thus, HM71224 is a potential novel therapeutic agent for rheumatoid arthritis in humans.